Lip print analysis in Malaysian Chinese population (Klang Valley): lipstick-cellophane tape technique - Noor Hazfalinda Hamzah,; Amalina Farhatul Farida Mohamad Seliman,; Khairul Osman,; Gina Francesca Gabriel, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cheiloscopy is recognised as a tool for personal identification due to its strength in criminalistics. In this study, the lip print of Malaysian Chinese population in Klang Valley was used for sex determination using lipstick-cellophane technique. 412 subjects (203 males and 209 females) were selected conveniently. Lipstick was first applied on the lips and the lip print was lifted using cellophane tape prior to pasting them onto a plain A4 paper and analysis using magnifying glass. Six topography areas of lip prints were classified using Suzuki and Tsuchihashi’s classification, including upper left, upper middle, upper right, lower right, lower middle and lower left. Chi-square test showed that all lip sections were significantly different from each other (p < 0.05). Type II was the dominant pattern in four lip sections for both sexes: Upper left (male 81.3%, female 57.4%), upper right (male 71.9%, female 42.9%), lower left (male 98.0%, female 90.0%) and lower right (male 96.1%, female 86.1%). Type IV was the dominant pattern for both middle part of the lips; upper middle (male 56.2%, female 50.7%) and lower middle (male 62.6%, female 50.2%). This finding suggested that cheiloscopy could be used in aiding personal identification for forensic investigation.